1993
DOI: 10.1152/ajpgi.1993.265.4.g677
|View full text |Cite
|
Sign up to set email alerts
|

Proximal duodenal enterocyte transport: evidence for Na(+)-H+ and Cl(-)-HCO3- exchange and NaHCO3 cotransport

Abstract: The duodenum, in contrast to the jejunum, actively secretes HCO3- at a high rate, a process that protects the mucosa from acid/peptic injury. Our purpose was to define the mechanisms involved in HCO3- transport by studying the acid-base transport processes in isolated duodenal enterocytes. Individual rat duodenocytes, isolated by a combination of Ca2+ chelation and collagenase, attached to a collagen matrix were loaded with the pH-sensitive fluoroprobe 2',7'-bis(2-carboxyethyl)-5(6)-carboxyfluorescein acetoxym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
89
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 0 publications
3
89
0
Order By: Relevance
“…They found that HCO 3 Ϫ secretion and Cl Ϫ absorption were both higher in the proximal than in the distal colon, which is an early documentation of segmental heterogeneity of colonic HCO 3 Ϫ secretion. 28) When Yau and Makhlouf studied HCO 3 Ϫ secretion in everted mucosal sac preparations from rat colon, they found a significantly higher secretory rate in the descending than in the ascending part, and a dependence on extraluminal Cl Ϫ , which argued for a Cl Ϫ /HCO 3 Ϫ exchange process, but also for profound species differences. 29) The characterization of the electrolyte transport proteins involved in colonic HCO 3 Ϫ transport has offered the possibility to get insight into the molecular basis for the segmental differences in colonic electrolyte transport.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…They found that HCO 3 Ϫ secretion and Cl Ϫ absorption were both higher in the proximal than in the distal colon, which is an early documentation of segmental heterogeneity of colonic HCO 3 Ϫ secretion. 28) When Yau and Makhlouf studied HCO 3 Ϫ secretion in everted mucosal sac preparations from rat colon, they found a significantly higher secretory rate in the descending than in the ascending part, and a dependence on extraluminal Cl Ϫ , which argued for a Cl Ϫ /HCO 3 Ϫ exchange process, but also for profound species differences. 29) The characterization of the electrolyte transport proteins involved in colonic HCO 3 Ϫ transport has offered the possibility to get insight into the molecular basis for the segmental differences in colonic electrolyte transport.…”
Section: Introductionmentioning
confidence: 94%
“…The molecular nature of the pathway for HCO 3 Ϫ secretion in epithelia has been a subject of debate for decades, with focus in airway, gastroduodenal and pancreatic epithelia. [1][2][3][4][5] In all these tissues, a different composition of anion exchangers and anion conductances is expressed in the luminal membrane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there appear to be two potential mechanisms for HCO 3 -exit across the apical membrane. The first involves the activity of a Cl-HCO 3 exchanger (Brown et al, 1989;Isenberg et al, 1993;Spiegel et al, 2003;Wang et al, 2002), most likely a member of the SLC26 family of anion exchangers (Jacob et al, 2002;Wang et al, 2002), and may be associated with spontaneous HCO 3 -secretion by the duodenum (Spiegel et al, 2003). In addition, acid or secretagogues stimulate electrogenic HCO 3 -secretion, which is independent of Cl-HCO 3 exchanger activity (Seidler et al, 1997;Spiegel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%